Is Accurate N – Staging for Gastric Cancer Possible? - Vergadis, Chrysovalantis; Schizas, Dimitrios (Frontiers in Surgery, 2018)
Node stage (N stage) is of paramount importance for gastric cancer staging. Radiologically node status implies detection and characterization of suspect malignant lymph nodes. Clinically it might determine survival and alter therapeutic plans. A number of modalities, including computerized tomography, MRI, PET and endoscopic ultrasound are currently available. Using a multimodality strategy, accuracy ranges between 50–90% across various studies. Specificity and sensitivity varies with respect to method, number of positive lymph nodes, their location and other characteristics. Restaging after neoadjuvant therapy and staging of recurrence presents its own, particular challenges. Each method has its advantages and limitations and none of them alone is adequate enough for staging. While most of them are clinically well established, they are also active research topics. To overcome the aforementioned limitations a multidisciplinary, multimodality approach with emphasis on clinical staging and treatment plans is proposed.